Analisis Pengaruh Profesionalisme, Independensi dan Pengalaman Kerja Pada Kinerja Pengawas Internal (Panureksa) LPD - Putra, I Gede Alit; Jati, I Ketut (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p23, 2019)
This study aims to determine the effect of professionalism, experience and independence on LPD internal supervisory performance in the Abiansemal District of Badung RegencyIn order to produce good performance, professionalism, experience and an attitude of independence are needed in carrying out tasks to support the performance of a good supervisor. The research method is a quantitative method, while this research is an associative type of causality with the method of data collection using a questionnaire. Population and sample amounted to 102 respondents with saturated sampling method. The data analysis technique is multiple linear regression analysis. The results of the study indicate that professionalism, independence and work experience have a positive and significant effect on the performance of internal supervisors of all LPDs in Abiansemal District. So that according to role theory, having knowledge and experience will reduce the occurrence of role conflicts that can later affect performance. Keywords : Professionalism, independence, work experience, performance internal supervisor